Hierarchical nitrogen-doped flowerlike ZnO nanostructure and its multifunctional environmental applications - Bai, Hongwei (2013)
Hierarchical nitrogen-doped ZnO flowerlike nanostructures were synthesized on a large scale. These nanostructures were characterized by FESEM, HRTEM, XRD, FTIR, XPS, and TGA, and their suitability for multifunctional environmental applications was investigated. The experimental results demonstrated that the hierarchical N-doped ZnO flowerlike nanostructure enhances the photodegradation of methyl blue (MB) and acid orange 7 (AO7) by presenting a large specific surface area and high light utilization rate, inhibits the growth of bacteria without light irradiation, and increases the permeate flux when used in a membrane filtration system. These advantages of the hierarchical N-doped ZnO flowerlike nanostructure brings benefits to the environmental application fields.